2000
DOI: 10.1016/s0893-133x(00)00120-2
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Increase in Narp Protein Expression Following Repeated Electroconvulsive Seizure

Abstract: The delayed response to many psychiatric treatment regimens has focused attention on identifying enduring changes in gene expression following repeated stimulation that may contribute to these responses. Recent studies have identified Narp protein as a neuronal immediate early gene product that remains elevated in the hippocampus nearly 24 hours after a single episode of electroconvulsive seizure (ECS). To examine how Narp expression responds to repeated stimulation, we have examined the effect of repeated ECS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 18 publications
4
41
1
Order By: Relevance
“…16,17 A series of spaced ECS treatments was also shown to enhance the expression of Narp protein, an immediate early gene product that probably plays a regulatory role in the clustering of AMPA receptors at synaptic sites. 30 Although the expression of mRNA for the NR1 subunit was unchanged in our study, 28 ECS treatment has been shown to alter the expression of mRNA for other NMDA receptor subunits. Watkins et al 31 found that chronic ECS treatment produced an acute increase in mRNA for both the NR2A and NR2B subunits of the NMDA receptor in the dentate gyrus, although only the NR2B increase was sustained 24 h later.…”
Section: Molecular Mechanisms Underlying the Ecs Effectcontrasting
confidence: 59%
“…16,17 A series of spaced ECS treatments was also shown to enhance the expression of Narp protein, an immediate early gene product that probably plays a regulatory role in the clustering of AMPA receptors at synaptic sites. 30 Although the expression of mRNA for the NR1 subunit was unchanged in our study, 28 ECS treatment has been shown to alter the expression of mRNA for other NMDA receptor subunits. Watkins et al 31 found that chronic ECS treatment produced an acute increase in mRNA for both the NR2A and NR2B subunits of the NMDA receptor in the dentate gyrus, although only the NR2B increase was sustained 24 h later.…”
Section: Molecular Mechanisms Underlying the Ecs Effectcontrasting
confidence: 59%
“…In previous studies, we have demonstrated that this antibody is highly specific for Narp, as assessed by immunobloting of brain extracts and immunohistochemistry (Reti and Baraban, 2000;Reti et al, 2002a, b, c). Other primary antibodies used for immunohistochemistry were: rabbit polyclonal Arc (1 : 500; Lyford et al, 1995) and goat polyclonal c-Fos (1 : 100; Santa Cruz).…”
Section: Antibodiesmentioning
confidence: 86%
“…As a control for Arc immunostaining in the amygdala, one animal also received electroconvulsive shock (as described in Reti and Baraban, 2000) and was killed 4 h later for processing of hippocampal sections.…”
Section: Drug Treatmentsmentioning
confidence: 99%
“…Specific effects of antidepressants or electroconvulsive treatment have already been reported for immediate early genes and transcription factors such as c-fos, zif268, NGF1-A, phosphorylation of CRE-binding protein, DfosB, and Narp. [65][66][67][68][69][70][71][72] In our analysis, we identified four genes that were downregulated in response to both IMI and SJW. Such genes could be potential markers for predicting response to antidepressant treatment; however, the fact that genes are coordinately downregulated suggests there are specific combinations of transcriptional regulators that control the expression of these four genes.…”
Section: Discussionmentioning
confidence: 99%